Protective immunity to Shiga-like toxin I following oral immunization with Shiga-like toxin I B-subunit-producing Vibrio cholerae CVD 103-HgR. - Acheson, D W (1996)
This study addresses a mechanism for inducing systemic immunity to Shiga-like toxins by oral administration of a Shiga-like toxin I B-subunit-expressing Vibrio cholerae vaccine strain [CVD 103-HgR(pDA60)]. Two sets of three rabbits were given either CVD 103-HgR or CVD 103-HgR(pDA60) orally. All rabbits immunized with CVD 103-HgR(pDA60) developed neutralizing serum antibodies to Shiga-like toxin I. None of the controls developed such antibodies.